Analysing the application of “Reblocking” of informal settlements in the City of Ekurhuleni - Basson, Annelien (Department of Civil Engineering, 2020)
Dealing with the challenge of informal settlements is one of the biggest issues facing South Africa and other countries of the global South. There is an urgent need to document and reflect on attempts to intervene in informal settlements. This dissertation investigates and analyses the application of ‘reblocking’, a particular approach to informal settlement upgrading, in the City of Ekurhuleni in Gauteng Province, South Africa, and assess the extent to which it complies with the accepted principles of good informal settlement upgrading. Reblocking essentially involves the realignment of structures in an informal settlement to enable basic services to be delivered, and can also result in reduced fire risk and more usable communal spaces. The process of reblocking is also valuable as collaborative planning tool to build grassroots capacity. First of all, based on a review of the literature and interviews with practitioners and scholars, the principles of what can be regarded as ‘good’ informal settlement upgrading were collated. The policy context of upgrading in South Africa (particularly the Upgrading of Informal Settlements Programme) is reviewed, and the history of the reblocking approach in South Africa (first implemented by Slum Dwellers International with the City of Cape Town, and subsequently adopted by the City of Ekurhuleni) is examined. The case study of reblocking in Ekurhuleni Municipality is then discussed in detail. Finally, the dissertation compares the experiences of reblocking in Ekurhuleni with the principles of ‘good’ informal settlement upgrading and with the other South African approaches to reblocking, and makes recommendations for how informal settlements could be better addressed in Ekurhuleni (and elsewhere). The key findings of the dissertation are that, while reblocking can be very beneficial in terms of providing services and empowering communities, the approach used in Ekurhuleni is less participatory and thus has fewer social benefits than its counterpart in the City of Cape Town. In addition, all South African reblocking initiatives avoid providing de jure security of tenure, and can even decrease de facto security of tenure (as many reblocked settlements are still at risk of relocation), which negates one of the major advantages of initial public investment. The dissertation highlights that there is a need for transformed mindsets, policies and bureaucratic systemsthat are better aligned with the complex and dynamic nature of informal settlements, in view of the growing housing backlog in the CoE, South Africa and the global south.